Przestrzeń pozaziemska obszarem zainteresowania nauk o bezpieczeństwie. Kosmiczny wymiar bezpieczeństwa Polski - Kiszka, Krystian (De Securitate et Defensione. O Bezpieczeństwie i Obronności, 2016)
Security means to meet such needs as: the existence, survival, wholeness, identity, independence, peace, possession and confidence in development. In the twentieth century, mankind to satisfy its needs, went into the outer space. Currently, Earth orbit is full of satellites (communications, navigation, surveillance, meteorological, spy) which affect our daily lives, but also space garbage, which are a challenge for further expansion. Military competition during the Cold War led to the recognition that the space will be used only for peaceful purposes (Treaty on Principles Governing the Activities of States in the Exploration and Use of Outer Space, including the Moon and Other Celestial Bodies, 1967). Nowadays activities in space is also a source of innovations generating technological development. This is one of the tasks of Polish Space Agency, created in 2014.